(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
In the article, taking into account the specific features of the field of preschool education, the formation of the skills of the future preschool teacher on child hygiene - as a pedagogical problem, first consists in explaining the social nature of his profession.